2016
DOI: 10.1063/1.4966589
|View full text |Cite
|
Sign up to set email alerts
|

Low-dielectric layer increases nanosecond electric discharges in distilled water

Abstract: Electric discharge in liquids is an emerging field of research, and is involved into various environmental applications (water purification, fuel reforming, nanomaterial synthesis, etc.). Increasing the treatment efficiency with simultaneous decreasing of the energy consumption are the main goals of today’s research. Here we present an experimental study of nanosecond discharge in distilled water covered by a layer of dielectric material. We demonstrate through this paper that the discharge efficiency can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…They can be classified into two categories: thermal and non-thermal plasma sources. Non-thermal plasmas, including pulsed-nanosecond discharge [4][5][6], dielectric barrier discharge [7,8], and plasma jet [9], have been extensively investigated for liquid processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be classified into two categories: thermal and non-thermal plasma sources. Non-thermal plasmas, including pulsed-nanosecond discharge [4][5][6], dielectric barrier discharge [7,8], and plasma jet [9], have been extensively investigated for liquid processing.…”
Section: Introductionmentioning
confidence: 99%
“…When we take the example of in-liquid plasmas generated by nanosecond discharges, these discharges are generated with or without gaseous bubbles, and usually run in spark mode [16][17][18] (i.e., the plasma channel connects two electrodes) or in streamer mode [4][5][6] (i.e., the plasma channel is connected to one electrode). In the case of a spark mode, the plasma-electrode interaction is relatively strong, which leads to erosion issue [19][20][21] and reduces a lifetime of electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that a discharge at the interface of two dielectric liquids with different ε creates a plasma channel along the interface. [28] We found that this channel dissociated both liquids at the interface. In addition, when the location of a highvoltage anode was close to the interface between the two liquids, the local field intensity near the anode tip became strong, which facilitated the discharge and increased the plasma volume.…”
Section: Discussionmentioning
confidence: 75%
“…We recently showed that a discharge at the interface of two dielectric liquids with different ϵ creates a plasma channel along the interface . We found that this channel dissociated both liquids at the interface.…”
Section: Resultsmentioning
confidence: 90%
“…For this, we recently introduced a new method presenting significant benefits and could be instrumental in the synthesis of nanomaterials [29]. This method is based on the discharge in layered two immiscible liquids [34]. The basic physics of the method, as well as its experimental implementation are detailed in Section 2.…”
Section: Page 4 Of 23 Author Submitted Manuscript -Jphysd-116707r1mentioning
confidence: 99%